Questions and answers on the immuno-epidemiological surveillance of vaccine-preventable diseases - Enelis Reyes Reyes; Ronald Hernández Torres (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2017)
Full text (español)